Investigating Anti-Oxidative and Anti-Inflammatory Effects regarding Ethanol Extract of Allium Porrum L. in Rats with Type 2 Diabetes Mellitus - Nahid Najafi; Seyed Jalil Masoumi; Ali Akbar Nekooeian; Nader Tanideh; Siavash Babajafari; Hossein Khosravi-Boroujeni; Najmeh Maayeshi; Saeed Sherafatmanesh (Journal of Nutrition and Food Security)
Type 2 diabetes mellitus (T2D) is a common endocrine and metabolic disorder worldwide. Meanwhile, Allium Porrum L. (AP) has been recognized as one of the most eminent traditional herbal medicines with substantial health benefits. The aim of the present study is to evaluate anti-oxidative and anti-inflammatory effects of ethanol extract of AP in rats with T2D. Methods: 70 male Sprague-Dawley rats were randomly divided into 7 groups of 10 animals each. The study groups were as follows: The study groups were as follows: healthy control (HC); healthy control rats receiving 100 mg/kg of AP extract (HC.AP.100); diabetic control (DC); diabetic rats receiving 10 mg/kg metformin (DT.M.10); diabetic animals receiving 50 mg/kg of AP extract (DT.AP.50); diabetic rats receiving 100 mg/kg of AP extract (DT.AP.100); and  diabetic animals receiving 200 mg/kg of AP extract (DT.AP.200). Results: After 6 weeks of intervention, the level of serum malondialdehyde (MDA) and tumor necrosis factor alpha (TNF-α) were significantly increased (P=0.02) and (P=0.002), respectively; while superoxide dismutase (SOD) concentration was notably reduced (P=0.04) in DC.M.10 in comparison with that of the HC.AP.100 group. Also, compared to DC.M.10 group, all rats treated with metformin and AP showed a significant decrease in the level of MDA and TNF-α, along with an enhancement of SOD concentration (All P<0.001). Moreover, in comparison with DT.M.10, DT.AP.50, and DT.AP.100 treatments, the DT.AP.200 group revealed a significantly higher improvement in serum TNF-α concentration (P=0.04, P=0.003 and P=0.003, respectively). Conclusion: The findings revealed that the use of AP extract for 6 weeks may have beneficial effects on oxidative stress and inflammatory biomarkers in T2D-induced rat models